Study on the durability of engineered cementitious composites (ECCs) containing high-volume fly ash and bentonite against the combined attack of sulfate and freezing-thawing (F-T). (10th February 2020) - Zhao, Nan; Wang, Sheliang; Wang, Chunxuan; Quan, Xiaoyi; Yan, Qiangqiang; Li, Binbin
Highlights: The effects of FA and bentonite under freezing-thawing and sulfate are analyzed. Water, sodium sulfate, and magnesium sulfate under freezing-thawing are analyzed. SEM of ECC subjected to freezing-thawing in sulfate solutions is conducted. Abstract: This study investigated the durability of engineered cementitious composites (ECCs) containing bentonite and high-volume fly ash under coupled action of sulfate attack and freeze-thaw cycles. The proportions of fly ash and cement (FA/C) in ECCs were 1.2:1, 1.8:1 and 2.4:1, at the same time, in each FA/C ratio bentonite with three replacement ratio of 0%, 3% and 6% by weight was adopted, then specimens were exposed to water, 10% sodium sulfate solution, and 10% magnesium sulfate solution under 150 freeze-thaw cycles. In the experiment, compressive strength, relative dynamic elastic modulus (RDEM) and microstructure were evaluated for the resistance of the cement-based composite material in different sulfate solution under freeze-thaw cycles. The experimental results show that with the increase of the content of fly ash and bentonite, there is a corresponding reduction in the residual compressive strength after 150 freeze-thaw cycles, what's more, the residual compressive strength of specimens in the 10% magnesium sulfate solution was the highest after 150 freeze-thaw cycles. Moreover, the resistance of ECCs to freeze-thaw cycles and sulfate damage increased continuously during the first 50 freeze-thaw cycles, and then continued to decrease at the next 100 freeze-thaw cycles in 10% magnesium sulfate solution, while the performance of ECCs in water and 10% sodium sulfate solution continued to decrease during all the 150 freeze-thaw cycles. In addition, specimens with FA/C ratio of 1.8:1 and 0–3% bentonite showed obvious resistance to coupled attack of sulfate and freeze-thaw cycles. The deterioration of the durability of ECCs is related to both the freezing and thawing cycles and the sulfate attack. Meanwhile, durability performance of cement-based composites after 150 freezing and thawing cycles in different solutions is: 10% magnesium sulfate solution >10% sodium sulfate solution > water.